2017
DOI: 10.1186/s12887-017-0782-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with anaemia among children aged 6 to 59 months in Namutumba district, Uganda: a cross- sectional study

Abstract: BackgroundAnaemia is one of the major causes of death among children under five years in Africa, with a prevalence of 64.6% among pre-school children. In 2014, we conducted a cross-sectional study in Namutumba district in East-central Uganda to determine the prevalence and factors associated with anaemia among children aged 6 to 59 months.MethodsWe conducted a household survey in 376 randomly selected households. One child aged 6 to 59 months was randomly sampled from each selected household. A structured ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

36
64
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(105 citation statements)
references
References 28 publications
36
64
4
1
Order By: Relevance
“…According to this study, the prevalence of anemia is higher than the EDHS 2016 report of SNNPR under 5 years of age [27] and much lower than studies conducted in northern (66.6%) [8] and eastern (53.7%) [7] parts of Ethiopia, Cameron (66.7%), Sudan (86%) and Uganda (58.8%) [28][29][30] respectively. This might be attributed to seasonal food shortage since data were collected in spring which is a sunny season characterized by poor consumption of diversified foods and also due to the change made by the existing public health interventions, provision of health information through health extension workers.…”
Section: Discussionmentioning
confidence: 58%
“…According to this study, the prevalence of anemia is higher than the EDHS 2016 report of SNNPR under 5 years of age [27] and much lower than studies conducted in northern (66.6%) [8] and eastern (53.7%) [7] parts of Ethiopia, Cameron (66.7%), Sudan (86%) and Uganda (58.8%) [28][29][30] respectively. This might be attributed to seasonal food shortage since data were collected in spring which is a sunny season characterized by poor consumption of diversified foods and also due to the change made by the existing public health interventions, provision of health information through health extension workers.…”
Section: Discussionmentioning
confidence: 58%
“…Contrary to our study findings, a number of studies have reported a higher prevalence, for example, 78.4% in Ghana, 13 77.2% in Tanzania, 14 51.8% in Cape Verde, 10 and 58.8% in Namutumba District in Uganda. 19 …”
Section: Discussionmentioning
confidence: 99%
“…Anaemia and malaria are major contributors of childhood morbidity and mortality, particularly in sub-Saharan Africa [ 1 , 2 ]. The causes of anaemia in children are multifactorial and include malaria.…”
Section: Introductionmentioning
confidence: 99%